Solution of SPL Heat Conduction Model under Neumann Boundary Condition - T. N. Mishra; Atesh Singh (Scientific Research, New Technologies and Applications Vol. 6, 2024)
In this study, we will investigate the thermal wave propagation either by taking symmetric or asymmetric heating at the boundaries of finite thin film. Non-Gaussian heat sources are modelled as time-varying and spatially-decaying laser incidences. In this study, we present an unconditionally stable accurate finite difference scheme for Neumann (insulated) boundary condition which avoids the need of ghost point outside the boundary, unlike to the other finite difference schemes. The dimensionless form of model has been used for the complete analysis of model.